MiR-181a is associated with poor clinical outcome in patients with colorectal cancer treated with EGFR inhibitor. Issue 3 (4th October 2013) - Pichler, Martin; Winter, Elke; Ress, Anna Lena; Bauernhofer, Thomas; Gerger, Armin; Kiesslich, Tobias; Lax, Sigurd; Samonigg, Hellmut; Hoefler, Gerald
Abstract : Aims: miR-181a expression is frequently altered in different types of cancer. Members of the Wnt/β-catenin signalling pathway, which is commonly altered in colorectal cancer (CRC), have been reported as molecular interaction partners of miR-181. However, the role of miR-181a expression in CRC and its ability to predict survival and response to agents targeting the epidermal growth factor receptor (EGFR) have not been explored yet. Methods: In this study, we analysed 80 patients with wild type KRAS CRC undergoing treatment with the EGFR-targeting monoclonal antibodies cetuximab and panitumumab for metastatic CRC. The KRAS mutational status was determined by pyrosequencing and miR-181a expression was measured by quantitative RT-PCR in CRC tumour tissue and corresponding non-neoplastic colon tissue. The microRNA expression levels were correlated with clinicopathological characteristics. Cancer-specific survival was calculated by univariate and multivariate analyses, and progression-free survival (PFS) during treatment with EGFR-targeting agents was also evaluated. Results: A low miR-181a expression level was associated with poor differentiation of CRC (p=0.04). A Kaplan-Meier curve showed a decreased survival time for patients with low miR-181a expression (p=0.019). Low miR-181a expression was furthermore associated with poor PFS (p=0.015). Conclusions: In conclusion, our data suggest that the miR-181a expression level is associated with poor survival in patients with CRC. Furthermore, miR-181a expression might predict PFS in EGFR-targeted therapy.